A review of heating, ventilation and air conditioning technologies and innovations used in solar-powered net zero energy Solar Decathlon houses. (10th December 2019) - Ma, Zhenjun; Ren, Haoshan; Lin, Wenye
Abstract: Innovations in Heating, Ventilation, and Air Conditioning (HVAC) systems are continuously required to provide a better, healthier and more productive and sustainable built environment for building occupants with minimized energy or cost consumption. This paper provides an overview of the HVAC technologies and systems used in 212 solar-powered houses developed through 13 U.S. Department of Energy Solar Decathlon (SD) competitions. Some comments and discussions on the HVAC technologies and systems used in the SD competitions were also provided. The review was carried out based on the information available from the organizer's project reports and equipment summary, team project manuals, and construction drawings available on the SD official websites as well as the published research papers and textbooks. It was found that 84.9% and 89.6% of the competition teams used heat pumps for space heating and space cooling, respectively, among which air-to-air heat pumps were used by approximately 50% of the competition teams. A wide range of energy technologies such as phase change materials, night-time radiative cooling, evaporative cooling, desiccant dehumidification, and energy/heat recovery ventilators have been used to reduce the electricity consumption of the HVAC systems. Energy/heat recovery ventilators were used by more than 55% of the teams in each competition held after 2005. Phase change materials were also frequently used in the competitions held in Europe. The SD competitions provided an excellent platform to showcase innovations of the HVAC technologies in residential buildings.